Elektrikli araçların dağıtım şebekesine entegrasyonu - Özcan, Memduh Emrah (My University, 2019)
Temelde iki farklı grup altında toplanabilen elektrikli araçlar, hibrit ve sadece elektrikliaraçlar olmak üzere sınıflandırılmaktadır. Hibrit araç grubu, kendi içerisinde şarjedilebilen ve şarj edilemeyen araçlar olarak alt sınıflara ayrılmaktadırlar. Hibrit araçlarüzerinde fosil yakıtlı motor ve elektrik motoru olmak üzere iki farklı sistem mevcuttur.Sadece elektrik motorlu araçlar, isminden de anlaşılabileceği üzere sadece elektrikmotorları sayesinde hareket ettirilmektedir. Şarj edilebilen hibrit elektrikli araçlar vesadece elektrikli araçlar üzerinde şebekeden şarj edilerek doldurulmakta olan haricibatarya sistemleri mevcuttur. Bu batarya sistemlerinin beslenebilmesi için elektrikli araçşarj ekipmanları ve elektrikli araç şarj istasyonları kullanılmaktadır. Günümüz moderntoplumunda zamanın önemli bir değer olması sebebiyle de elektrikli araçların daha hızlışarj edilmelerine ihtiyaç günden güne artmaktadır. Bu sebepten elektrikli araçların şarjedilmesi esnasında aktarılan enerji ve şarj süresi büyük önem kazanmaktadır. Dünyaçapında bakıldığından elektrikli araçların şarj edilmesi için kullanılan belli başlı sistemlerön plana çıkmaktadır, bunların yanında bazı firmalar kendi markaları için özelgeliştirdikleri şarj sistemleri ile kendi kullanıcılarına daha hızlı şarj etme avantajısağlamaktadırlar. Farklı araç modellerinde çeşitli sistemler kullanılabildiği gibi kıtalarhatta ülkeler arasında dahi elektrikli araç şarj istasyonları farklılıklar göstermektedir.Araçların belirli standartlar içerisinde üretilmesi ve kullanılması gerekmektedir.Araçların şarj edilmesi için kullanılan şarj ekipmanı ve şarj istasyonlarının elektrikşebekeleri üzerinden beslenmeleri gereklidir. Elektrikli araçların ve şarj sistemlerininşebekeye entegrasyonu büyük önem taşımaktadır. Çünkü elektrik şebekelerinin elektrikliaraç şarj işlemleri için gereken güç talebini karşılaması ve şebekede bulunan elektrikkalitesini etkilememesi gerekmektedir. Elektrikli araç şarj istasyonlarının yasal sınırlarile belirlenmiş olan harmonik seviyelerini sağlaması ve şebekedeki enerjini kalitesiüzerinde olumsuz etki oluşturmaması beklenmektedir.Bu çalışmada elektrikli araçların şebeke enerji kalitesi üzerindeki etkileri üzerindedurulmuştur. Farklı araç modellerinin çeşitli şarj istasyonları kullanılarak şarj edilmesisonucunda oluşturdukları harmonik seviyeleri pek çok kaynaktan toplanarakdeğerlendirilmiştir. Çalışma kapsamında elektrikli araç şarj sistemlerinin şebekeye olanetkilerinin incelenebilmesi için Çanakkale Onsekiz Mart Üniversitesi Terzioğlu Kampüsübaz alınarak Digsilent zerinde model oluşturulmuştur. Kurgulanansimülasyonda kampüs içerisinde şebekeye kaç adet elektrikli araç şarj istasyonubağlanabileceği ve kaç araca hizmet verilebileceği konusu incelenmiştir. İlerleyenyıllarda elektrikli araç kullanımının ve üniversite popülasyonunun artması sebebiyletrafolar üzerinde yoğunluk oluşması ihtimali değerlendirilmiştir. Bu kapsamda yapılançalışmada, trafoların %100-%120-%150 değerlerine kadar yüklenmesi durumundaşebeke üzerine yerleştirilebilecek elektrikli araç şarj istasyonu adetleri konusuçalışılmıştır.

Electric vehicles, which can basically be grouped under two different groups are classifiedas hybrids and battery electric vehicles. Hybrid vehicles are divided into sub-classes asnon-rechargeable vehicles. They can be fed on two different systems as fossil fuel engineand electric motor on hybrid vehicles. Only the electric motor vehicles can be moved byelectric motors. Rechargeable hybrid electric vehicles and only electric motor vehicleshave external charged battery systems which sould be charged from the grid. Electricvehicle charging equipment and electric vehicle charging stations are used for the feedingof these battery systems. When looking at the equipment used for charging electricvehicles, different types of charging equipment can be seen. In today's modern society,due to the fact that time is an important value, the need for faster charging of electricvehicles is increasing day by day. For this reason, the transferred energy and charge timeduring charging of electric vehicles is of great importance. The main systems used for thecharging of electric vehicles come to the fore. Besides, some companies can provide fastercharging advantage to their users with the charging systems they have developed speciallyfor their brands. Different systems are used for different vehicle models, even incontinents and countries, there are differences in electric vehicle charging stations. Thesedifferences became more apparent with the introduction of electric vehicles. Vehiclesmust be produced and used within certain standards. Manufacturers of electric vehicleand electric vehicle charging equipment are expected to meet these standards. Chargingstations used for the charging of vehicles must be supplied via electrical networks. In thiscontext, the integration of electric vehicles into the grid is of great importance. Theelectrical networks to which the car charging systems are connected must meet the powerdemand for charging. In addition, the electricity quality in the network should not beaffected by the vehicle charging stations. Harmonic levels determined by legal limits areexpected to be provided by electric vehicle charging stations. These systems are notexpected to have a negative impact on the quality of energy.In this study, the effects of electric vehicles on grid quality are discussed. The voltage andcurrent harmonic levels generated by charging different vehicle models by using differentcharging stations have been collected and evaluated from many sources. In this study, inorder to investigate the effects of electric vehicle charging systems on the grid, a modelwas created on the Digsilent program based on the Çanakkale Onsekiz Mart UniversityTerzioğlu Campus. In the simulation, how many electric vehicle charging stations can beconnected to the network and how many vehicles can be serviced in the campus topicsare examined. In the following years, due to the increase in the use of electric vehiclesand the increase of the university population, the intensity of the transformers wereevaluated. In this study, the number of electric vehicle charging stations that can besupplied over the network in case the transformers are loaded to 100% -120% -150% arestudied. Finally, the comparison of the use of electric and fossil fuel vehicles has beenmade economically, and the economic and environmental effects of electric vehicles havebeen studied.
Keywords: Electric vehicle charging stations; Electric vehicle components; Electric vehicles; Electrical distribution network; Elektrik Dağıtım Şebekesi; Elektrikli araç bileşenleri; Elektrikli araç şarj istasyonları; Elektrikli araçlar; Güç Sistemleri; Güç transformatörleri; Power systems; Power transformers